Retrospective analysis of the orbits of asteroids colliding with the Earth - Kholshevnikov, Konstantin S.; Balyaev, Ivan A.; Sokolov, Leonid L.; Eskin, Boris B. (Vestnik of Saint Petersburg University. Mathematics. Mechanics. Astronomy, 2021)
In this paper, we consider the trajectories of real and model asteroids that lead to collisions with the Earth. They highlight the close approaches to the Earth that precede the impact. The presence of such approaches allows you to detect a dangerous object in advance, clarify its orbit, and also use the effect of a gravitational maneuver to economically prevent an asteroid from hitting the Earth. The article considers various families of collision trajectories: possible trajectories of real dangerous asteroids, as well as model ones trajectories that are not linked to a specific object. It is shown that in the first case, the approaches preceding the collision are noticeably greater.